Combination of mesenchymal stem cell sheet with poly-caprolactone nanofibrous mat and Gelfoam increased osteogenesis capacity in rat calvarial defect - Behnaz Banimohamad-Shotorbani; Reza Rahbarghazi; Seyedhosein Jarolmasjed; Ahmad Mehdipour; Hajar Shafaei (BioImpacts)
Introduction: To date, different strategies have been used for co-transplantation of cell-loaded biomaterials for bone tissue regeneration. This study aimed to investigate the osteogenic properties of adipose-derived-mesenchymal stem cell (AD-MSC) sheets combined with nanofibrous poly-caprolactone (PCL) mat and Gelfoam in rats with calvarial bone defect. Methods: Calvarial critical-size defects were induced in male rats. Animals were classified into Control, Gelfoam, Gelfoam/PCL nanofiber, Gelfoam/AD-MSC sheet, and Gelfoam/PCL nanofiber/AD-MSC sheet groups. After 3 months, rats were sacrificed and the regeneration rate was evaluated. Results: Almost all groups showed bone regeneration properties, but the volume of newly formed bone was higher in groups that received Gelfoam/AD-MSC and Gelfoam/PCL nanofiber/AD-MSC sheets (P < 0.05). The application of Gelfoam/PCL nanofiber/AD-MSC sheets not only increased bone thickness, bone volume/total bone volume (BV/TV) ratio, strong Hounsfield Unit (HU), but also led to the formation of ossified connective tissue with wrinkled patterns. Conclusion: The current study indicated that the Gelfoam/PCL nanofiber/AD-MSC sheet provides a suitable platform for effective osteogenesis in calvarial bone defects.